Laminar-turbulent transition prediction in the presence of surface imperfections. (1st January 2014) - Perraud, Jean; Arnal, Daniel; Kuehn, Winfried
Renewed interest in practical laminar flow control has motivated a number of European research activities in these last years. Laminar wings design now includes the question of laminar flow 'resistance' to small surface deformations and accidents in surface quality, for which prediction tools are needed. This paper presents several models developed for predicting the impact of surface deformations on laminarity. Comparisons to large Reynolds number experiments are also included.